2020
DOI: 10.1109/mis.2020.3026430
|View full text |Cite
|
Sign up to set email alerts
|

The Era of Intelligent Recommendation: Editorial on Intelligent Recommendation with Advanced AI and Learning

Abstract: Sydney & IT IS OUR pleasure to share with you this special issue on intelligent recommendation with advanced artificial intelligence (AI) and learning, which includes eight articles published in the September/October issue of IEEE Intelligent Systems (IS). After our announcement in early August 2019 for this special issue, we received 40 submissions, only 8 ones out of which are accepted to be included in this special issue. After a long period of hard-work of review from anonymous reviewers and careful revisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(10 citation statements)
references
References 10 publications
0
10
0
Order By: Relevance
“…As part of the era of artificial intelligence (AI) and big data, specialized issues have been published to explore complex data, advanced AI, and combinations with RSs. A special issue [25] aimed to complement these discussions and inspire readers to tackle existing and emerging challenges in building RSs mostly focused on AI techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…As part of the era of artificial intelligence (AI) and big data, specialized issues have been published to explore complex data, advanced AI, and combinations with RSs. A special issue [25] aimed to complement these discussions and inspire readers to tackle existing and emerging challenges in building RSs mostly focused on AI techniques.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The role of data mining techniques in this system is to analyze students' learning behaviors and discover potential patterns and trends [12]. For example, by analyzing historical data, the system can identify which course content has the greatest impact on student learning outcomes or which types of programs are more motivating and engaging [13]. Implementing such a recommender system requires consideration of several aspects.…”
Section: Introductionmentioning
confidence: 99%
“…However, traditional graph perturbation methods mainly anonymize graphs in high‐dimensional space, ignoring the fact that low‐dimensional representations can reveal private information. Researchers found that attackers can use GNN‐based, 2 deep learning based, 3 reinforcement learning based 4 or other corresponding approaches 5 to infer privacy information about certain nodes from low‐dimensional graph representations. For instance, in Figure 1A, a user chose to hide his attribute location and social relationships, which have been removed from the published anonymous graph.…”
Section: Introductionmentioning
confidence: 99%